Investing and Establishing a High-Technology Manufacturing Operations in Indonesia - Siew, Samuel (2006)
For many companies, globalization is an inevitable process - driven by competition, lack of resources in home location, and the need for greater level of profits. The success and survival of many modern companies depend on how well they globalize. Regardless of the motivation to go abroad, the process of internationalization is one of the most difficult strategies to implement operationally. Choices have to be made, risks identified, hurdles cleared, reputation protected, and transition flawlessly executed. Failure in globalizing can be as disastrous as the failure to globalize. While companies are clear on the need to expand abroad, the process by which to successfully do so are, more often that not, less than clear. The problem is even larger when it comes to establishing significant presence such as a large manufacturing operation, and doing it in developing countries.